Early Life Stress Associated With Increased Striatal N-Acetyl-Aspartate: Cerebrospinal Fluid Corticotropin-Releasing Factor Concentrations, Hippocampal Volume, Body Mass, and Behavioral Correlates. (April 2018) - Coplan, Jeremy D.; Lu, Dunyue; El Sehamy, Alexander M.; Tang, Cheuk; Jackowski, Andrea P.; Abdallah, Chadi G.; Nemeroff, Charles B.; Owens, Michael J.; Mathew, Sanjay J.; Gorman, Jack M.
Introduction: Using proton magnetic resonance spectroscopy imaging, the effects of early life stress on nonhuman primate striatal neuronal integrity were examined as reflected by N -acetyl aspartate (NAA) concentrations. NAA measures were interrogated through examining their relationship to previously documented early life stress markers—cerebrospinal fluid corticotropin-releasing factor concentrations, hippocampal volume, body mass, and behavioral timidity. Rodent models of depression exhibit increases in neurotrophic effects in the nucleus accumbens. We hypothesized that rearing under conditions of early life stress (variable foraging demand, VFD) would produce persistent elevations of NAA concentrations (in absolute or ratio form) in ventral striatum/caudate nucleus (VS/CN) with altered correlation to early life stress markers. Methods: Eleven bonnet macaque males reared under VFD conditions and seven age-matched control subjects underwent proton magnetic resonance spectroscopy imaging during young adulthood. Voxels were placed over VS/CN to capture nucleus accumbens. Cisternal cerebrospinal fluid corticotropin-releasing factor concentrations, hippocampal volume, body mass, and response to a human intruder had been previously determined. Results: VFD-reared monkeys exhibited significantly increased NAA/creatine concentrations in right VS/CN in comparison to normally reared controls, controlling for multiple comparisons. In comparison to controls, VFD cerebrospinal fluid corticotropin-releasing factor concentrations were directly associated with right VS/CN absolute NAA. Left hippocampal volume was inversely associated with left VS/CN NAA/creatine in VFD reared but not in controls. Disruption of a normative inverse correlation between left VS/CN NAA and body mass was noted in VFD. Only non-VFD subjects exhibited a direct relationship between timidity response to an intruder and right VS/CN NAA. Conclusion: Early life stress produced persistent increases in VS/CN NAA, which demonstrated specific patterns of association (or lack thereof) to early life stress markers in comparison to non-VFD subjects. The data are broadly consistent with a stable nonhuman primate phenotype of anxiety and mood disorder vulnerability whereby in vivo indicators of neuronal integrity, although reduced in hippocampus, are increased in striatum. The findings may provide a catalyst for further studies in humans and other species regarding a reciprocal hippocampal/nucleus accumbens relationship in affective disorders.